Teori Perkembangan Pada Anak Usia Dini Menggunakan Teori Piaget - Artamevia, Reva Jovita; Aziza, Rizka Nur; Firdaus, Putri Sakinah Bayti (Jurnal Ilmiah Wahana Pendidikan, 2024)
Piaget introduced a number of ideas and concepts to describe and explain the changes in logical thinking he observed in children and adults. Cognitive development starts from concrete thinking processes to higher levels, namely abstract and logical concepts. Piaget believed that children are naturally interested in the world and actively seek out information that can help them understand that world. As an expert who conducted a lot of research on the level of development of human cognitive abilities, Piaget stated in his theory that human cognitive abilities consist of four stages starting from birth to adulthood. The stages and sequence apply to all ages but the age at which someone begins to enter a certain stage is not the same for everyone